Anemia in Male with Type 2 Diabetes Mellitus (Bangladesh Medical Journal, 2019)
Diabetes mellitus (DM) is the leading cause of many chronic diseases. Anemias in men with diabetes mellitus greatly contribute to the pathogenesis and progression of cardiovascular disease and aggravate diabetic nephropathy and retinopathy. The present study was carried out to estimate the Hb level, to determine the total count of RBC and reticulocyte count to evaluate the anemia and FBG & HbA1c to assess their glycemic status. The cross-sectional study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka from January, 2011 to December, 2011. Total 90 male subjects were selected with the age ranging from 40 to 60 years. Among them 60 subjects were diabetic, 30 subjects were with controlled (B1) and other 30 subjects with uncontrolled (B2) type 2 diabetes mellitus. They were selected from Outpatient Department of BIRDEM Hospital by random basis. And the rest 30 age-matched, healthy non-diabetic male subjects were considered as control group (A) for comparison. They were selected from Dhaka City through personal contact. For statistical analysis unpaired Student’s t-test was performed. The result was expressed as mean (±SD) among the groups. In this study, there are significant decrease in Hb level, total RBC count and increase in reticulocyte count in study groups. The prevalence of anemia is high in patients with type 2 DM, which affects quality of life of diabetic patients and is associated with disease progression and co-morbidities that contribute significantly to the increasing risk of cardiovascular diseases.Bangladesh Med J. 2017 Sep; 46 (3): 80-84